Design and Research of the Walkling Mechanism of the Stair Climbing Robot based on the Deformable Wheel Structure - Yang Ping; Liu Yuankai; Zhao Meixiang (Jixie chuandong)
To solve the problem of freightage in the situation of walk-up building,a type of intelligent stair-climbing robot with a new-type walking mechanism is developed. It puts deformable wheel into use which apply three groups of crank rocker mechanism to realize the deformation association and achieve the purpose of climb stairs. Firstly,the design process of walking mechanism is illustrated in details. Secondly,through the simulation research,the rationality of the designed structure for deformable wheel is analyzed. Finally,the physical prototype is made and the climbing test is achieved,which testified the feasibility of the design.